2022
DOI: 10.1002/anie.202208771
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Persistent Polarization Change in a Spin Transition Crystal

Abstract: Using light as a local heat source to induce a temporary pyroelectric current is widely recognized as an effective way to control the polarization of crystalline materials. In contrast, harnessing light directly to modulate the polarization of a crystal via excitation of the electronic bands remains less explored. In this study, we report an FeII spin crossover crystal that exhibits photoinduced macroscopic polarization change upon excitation by green light. When the excited crystal relaxes to the ground state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 82 publications
0
22
0
Order By: Relevance
“…5b, the polarization change (Δ P ) gradually increased to 0.45 μC cm −2 upon further heating, with a two-step abrupt change found in the temperature range between 90 and 130 K. The polarization change of 1 is comparable to non-ferroelectric molecular compounds such as spin-crossover (SCO) molecular crystals ([Fe(L) 2 (ClO 4 ) 2 ] (L = propyl-2,6-di(1 H -pyrazol-1-yl)isonicotinate), Δ P = 0.45 μC cm −2 ). 51…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5b, the polarization change (Δ P ) gradually increased to 0.45 μC cm −2 upon further heating, with a two-step abrupt change found in the temperature range between 90 and 130 K. The polarization change of 1 is comparable to non-ferroelectric molecular compounds such as spin-crossover (SCO) molecular crystals ([Fe(L) 2 (ClO 4 ) 2 ] (L = propyl-2,6-di(1 H -pyrazol-1-yl)isonicotinate), Δ P = 0.45 μC cm −2 ). 51…”
Section: Resultsmentioning
confidence: 99%
“…5b, the polarization change (ΔP) gradually increased to 0.45 μC cm −2 upon further heating, with a two-step abrupt change found in the temperature range between 90 and 130 K. The polarization change of 1 is comparable to non-ferroelectric molecular compounds such as spincrossover (SCO) molecular crystals ([Fe(L) 2 (ClO 4 ) 2 ] (L = propyl-2,6-di(1H-pyrazol-1-yl)isonicotinate), ΔP = 0.45 μC cm −2 ). 51 To support the structural origin of the pyroelectric current, we investigated the variation in the molecular dipole moment corresponding to the scissor-like motion with density functional theory (DFT) calculations. The calculation results revealed that the dipole moments of part B in the disordered structure are 14.877 D (90 K) and 16.020 D (260 K) (Fig.…”
Section: Pyroelectric Effectmentioning
confidence: 99%
“…Finally, the grand old phenomenon of SCO continues to evolve keeping abreast with the contemporary developments in molecular magnetism and related topics. 5,[28][29][30][31][32][33][34][35][36][37][38][39] We are happy that the topic has chosen us to express interesting facets, as discussed in this script.…”
Section: Discussionmentioning
confidence: 99%
“…Using this opportunity, a new field of magnetoelectric (ME) coupling in molecule‐based SCO materials has recently emerged where magnetic field H influences the electric polarization P and dielectric constant and/or the electric field E influences the magnetization M . [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] The coupling can be used in a numerous of technological applications, such as magnetic sensors, tunable antennas, energy harvesting, computing, and data storage[ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] with the important advantage that in these insulating materials the large power dissipation from electric currents in conducting materials is eliminated. [ 19 , 22 , 27 , 28 ] In contrast to inorganic materials, the sub‐field of ME coupling in molecular materials and SCO is relatively new.…”
Section: Introductionmentioning
confidence: 99%